1995
DOI: 10.1002/ps.2780440210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fenpiclonil on phosphorylation of glucose in Fusarium sulphureum

Abstract: The phenylpyrrole fungicide fenpiclonil inhibited the metabolism of glucose in mycelium of Fusarium sulphureum Schlecht at a concentration which only slightly inhibited mycelial growth (EC,,). At the same concentration, fenpiclonil also inhibited accumulation and, to a greater extent, phosphorylation of 2-deo~y[U-'~C]glucose in starved mycelium loaded with unlabelled 2deoxyglucose. Fenpiclonil did not affect cell-free phosphorylation of 2deoxyglucose or the ATP content of mycelium. Therefore, the primary mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Exposure to high doses of fenpiclonil (over 10-fold EC 50 concentrations) induces the accumulation of amino acids and monosaccharides (Jespers et al, 1993). Conversely the exposure to sub-lethal doses of phenylpyrroles seems to inhibit the incorporation of mono-saccharides into macromolecules (Jespers and De Waard, 1994) but also to stimulate biosynthesis and intracellular accumulation of glycerol and mannitol (Jespers and De Waard, 1995; Pillonel and Meyer, 1997). In order to precise the enzymatic step inhibited by phenylpyrroles, Jespers and De Waard (1995), studied the fate of radioactively labeled 2-deoxyglucose.…”
Section: Effect Of Phenylpyrroles On Target Fungi – Mode Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to high doses of fenpiclonil (over 10-fold EC 50 concentrations) induces the accumulation of amino acids and monosaccharides (Jespers et al, 1993). Conversely the exposure to sub-lethal doses of phenylpyrroles seems to inhibit the incorporation of mono-saccharides into macromolecules (Jespers and De Waard, 1994) but also to stimulate biosynthesis and intracellular accumulation of glycerol and mannitol (Jespers and De Waard, 1995; Pillonel and Meyer, 1997). In order to precise the enzymatic step inhibited by phenylpyrroles, Jespers and De Waard (1995), studied the fate of radioactively labeled 2-deoxyglucose.…”
Section: Effect Of Phenylpyrroles On Target Fungi – Mode Of Actionmentioning
confidence: 99%
“…In the presence of fenpiclonil, [ 14 C]-2-deoxyglucose accumulated intracellularly, while the intracellular concentration of [ 14 C]-2-deoxyglucose-phosphate diminished indicating the inhibition of hexokinase activity during exposure of the mycelium to the phenylpyrrole. When the authors performed the same assay on crude mycelial extracts, they only observed a minor reduction of [ 14 C]-2-deoxyglucose phosphorylation under high concentrations of fenpiclonil, withdrawing the cytoplasmic hexokinase as sole or direct target of fenpiclonil (Jespers and De Waard, 1995). …”
Section: Effect Of Phenylpyrroles On Target Fungi – Mode Of Actionmentioning
confidence: 99%
“…Wild-type N. crassa strains treated with fenpiclonil and fludioxonil at concentrations that inhibited fungal growth by 50% accumulated high concentrations of intracellular glycerol (26). Some Ustilago maydis and F. sulphureum mutants resistant to phenylpyrrole fungicides also were sensitive to high osmotic pressure (13,14). These studies suggested that there is a relationship between osmoregulation and phenylpyrrole fungicide resistance.…”
mentioning
confidence: 98%
“…They are broadspectrum fungicides used to control a variety of important plant-pathogenic fungi. Previous studies with Fusarium sulphureum Schlecht indicated that fenpiclonil inhibited the transport of monosaccharides and caused intracellular accumulation of polyols, such as glycerol and mannitol (13,14). Wild-type N. crassa strains treated with fenpiclonil and fludioxonil at concentrations that inhibited fungal growth by 50% accumulated high concentrations of intracellular glycerol (26).…”
mentioning
confidence: 98%
“…Biological activity of pyrrolnitrin at low concentrations was demonstrated to be due to the uncoupling of oxidative phosphorylation in Neurospora crassa and at higher concentrations due to inhibition of electron transport both in the flavin region and through cytochrome c oxidase (6). Recently, it was reported that pyrrolnitrin leads to glycerol accumulation and stimulation of triacylglycerol synthesis, resulting in leaky cell membranes and concomitant breakdown of biosynthetic activity followed by cessation of cell growth (7).…”
mentioning
confidence: 99%